2014
DOI: 10.1007/s00134-014-3218-7
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure in the critically ill performing early physical therapy

Abstract: The critically ill have increased REE according to inflammation defined by CRP. Increased energy requirement for physical activity was only present for active exercise and seems to differ from that in the healthy population. For the exercise duration and intensity tested, nutritional adjustment is not indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 36 publications
5
29
0
2
Order By: Relevance
“…Our study found that the baseline EE estimated by the Harris and Benedict formula 15 was significantly lower than that measured by IC. This finding corroborates the indication not to use this formula in critically-ill patients, 7,[16][17][18] and in patients with AKI. 19 The best way to assess the energy needs of critically-ill patients with AKI is by means of IC.…”
Section: Discussionsupporting
confidence: 85%
“…Our study found that the baseline EE estimated by the Harris and Benedict formula 15 was significantly lower than that measured by IC. This finding corroborates the indication not to use this formula in critically-ill patients, 7,[16][17][18] and in patients with AKI. 19 The best way to assess the energy needs of critically-ill patients with AKI is by means of IC.…”
Section: Discussionsupporting
confidence: 85%
“…[16,[21][22][23][24] Of these 6 reports, there were 3 case series, [21][22][23] 1 case control study, [24] and 2 randomized clinical trials (RCTs), [16,20] with sample sizes varying from 16 [24] to 90 [16] enrolled patients. These reports included evaluation of single cycling sessions, [21][22][23] cycling as part of a rehabilitation therapy protocol, [20] cycling added to usual-care PT interventions, [16] and cycling augmented by electrical stimulation. [24] Reported cycling session duration was <5, [20,22] …”
Section: Discussionmentioning
confidence: 99%
“…However, this equation remained with poor degree of reproducibility (ICC 0.18), and poor agreement with IC (limits of agreement large, range -1,472 to 1,627.6 kcal/day). Other studies also showed low concordance and accuracy between the equation HB and IC, even using the injury factor [6,13,16,[33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%